Hasil Belajar Murid Kelas IV SDN 07 Belakang Balok Kota Bukittinggi pada Pembelajaran IPAS Materi Sejarah dengan Model Teams Games Tournament - Niken Sekar Kinasih; Masniladevi Masniladevi; Afriza Media; Ummiatul Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the improvement of student learning outcomes through the implementation of the Teams Games Tournament (TGT) model in the history material of science learning in grade IV of SDN 07 Belakang Balok, Bukittinggi City. The study used a qualitative and quantitative approach in the form of classroom action research carried out in two cycles, each including the planning, implementation, observation, and reflection stages. The research subjects consisted of 21 grade IV students, the class teacher as observer, and the researcher as learning practitioner. The results showed an increase in each indicator. The average assessment of the lesson plan increased from 87.45% (good category) in cycle I to 95.83% (very good) in cycle II. The implementation of learning in the teacher aspect increased from 89.25% (good) to 96.42% (very good), while the student aspect increased from 78.55% (sufficient) to 92.85% (very good). Student learning outcomes also increased from an average of 78.72 (sufficient) in cycle I to 89.55 (good) in cycle II. The limitations of this study lie in the relatively small number of subjects, the limited coverage of material on a single history topic, and the implementation of only two cycles, which do not yet reflect long-term impacts. Based on these findings, it is recommended that the TGT model be applied to a wider range of materials and levels and combined with a variety of learning media to increase student engagement sustainably.